Ruptured Hemorrhagic Hepatic Cyst: An Unusual Case Report - Amaral, Maria João (2020)
Background: Hemorrhagic rupture of a hepatic cyst is rare. To date, very few cases have been reported in the literature. Case Report: A patient with a history of a suspected liver hydatid cyst presented to the emergency department with abdominal pain and fever. She was admitted with the presumptive diagnosis of acute cholecystitis. During hospitalization, the patient presented with hemodynamic instability and abrupt worsening of the abdominal pain. The abdominal angio- chemotherapy scan showed an abundant free peritoneal effusion and an apparent effacement of the anterior wall of a hepatic cyst of 16 cm. The patient underwent an exploratory laparotomy, deroofing of the cyst, and peritoneal lavage. The anatomopathological results showed a simple hepatic cyst. Discussion: Hemorrhagic rupture of simple hepatic cysts is a life-threatening complication and, although rare, should be included in the differential diagnosis of sudden abdominal pain in patients with a history of simple hepatic cysts.